CHARACTERIZATION OF VARIOUS VIRULENCE PROPERTIES OF DRUG-RESISTANT KLEBSIELLA ISOLATES: AN IN VITRO STUDY AMONG SUPERBUGSâ€ - Devrari, Jitendra Chandra; Pai, Vidya (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study was to evaluate the various virulence factors among all extended-spectrum beta-lactamase (ESBL)-producing Klebsiella isolates. Methods: Klebsiella species (n=201) isolated from various non-repeated clinical samples from October 2016 to May 2017 were collected and identified by biochemical method and confirmed by BD Phoenix. Antibiotic susceptibility test was performed by Kirby-Bauer disc diffusion method, and ESBL detection was done by combined disc diffusion method. Capsule detection was done by nigrosin dye staining, hypermucoviscosity was done by string test, biofilm was performed by microtiter plate assay, and hemagglutination was performed with human erythrocytes treated with tannic acid. Results: Among 201 ESBL-producing Klebsiella isolates, 63.2 % were multidrug resistance and 24.4% were extensively drug-resistant. Among these isolates, Klebsiella infection is more in older patients. All isolates were (100%) positive for capsule and siderophores production. Of all 201 isolates, 14 (7%) were strong, 61 (30.3%) were moderate, and 104 (51.8%) were weak biofilm producers. Among these isolates, 36 (17.9%) were type 1 fimbriae, 140 (69.7%) were type 3 fimbriae, and only 17 (8.5%) were positive for hypermucoviscosity. Conclusion: Several virulence factors were studied, in which biofilm with fimbriae is the main cause for the resistance of antibiotics. Bacterial resistance profile found to be high with ESBL production and multiple drug resistance in the majority of the Klebsiella isolates, which is a result of improper antibiogram schedule and their virulence property.